Model of Organizational Structure for University Institutes Binding with the Venezuelan Socioeconomic Reality - Pertuz Belloso, Rafael (2014)
The present study is aimed at proposing a model of organizational structure for university institutes binding with the Venezuelan socioeconomic reality. This is a descriptive non-experimental cross-sectional research study. The study population included 746 professors and administration from the Cabimas and Maracaibo Technological Universities. Data was collected using a questionnaire consisting of 54 items and analyzed using the percentage frequency distribution. Results obtained indicate the sub-systems not integrated in the studied institutions, coexisting bureaucratic structural typologies, and a clear decontextualized implementation of the nation’s plans, which shows low relevance and relationship to the Venezuelan socioeconomic reality. To remedy this situation, a mixed departmental/matrix organizational structure model was designed that integrates the department into a matrix network linking teaching, research, and social action projects. The implementation of this model was proposed in three stages or phases in order to achieve the operational characteristics of the departmental model.